What should be the age limit for the children to access medications on their own?: Review [İlaca kendilerinin erişimi bakımından çocukların yaş sınırı ne olmalıdır?] - AKICI, AHMET; TIPLAMAZ, SITKI (Turkiye Klinikleri, 2016)
The questions that when and how children should access medications could not be answered sufficiently in both Turkey and worldwide. In this review, the issue of access to medications for children is discussed through critical age limit to provide drug/product on their own. The article is addressed primarily to the relevant terms and regulations. Medical, social and legal dimensions of the age limit of access to medications are emphasized regarding cognitive development and ability to distinguish in children. Two separate suggestions which can be used have been introduced, considering the children’s complex development process including their cognitive development and their ability to distinguish. In the first suggestion, the critical age limit was set at 16; over this age could be similar to adults in terms of issue of access to medications; in 12-15-age group, access to medications could be determined based on acquired the ability to direct their behaviour; <12-year-old was defended by no means out of reach of drugs on their own. In the second suggestion, with a relatively conservative approach, critical age limit was set at 18; in 16-17-age group, access to medications could be determined based on acquired the ability to direct their behaviour; <16-year-old was defended by no means out of reach of drugs on their own. There will also be need to be taken of other mitigating precautions for distress that may be occur with the adoption one of these alternative suggestions regarding the age limit. © 2016 by Türkiye Klinikleri.
Keywords: Age factors; Child welfare; Medicine; Pharmacy